Analisis faktor-faktor yang mempengaruhi produksi karet di Kecamatan Jaluko Kabupaten Muaro Jambi (studi kasus Desa Muhajirin) - Afriani Dalimunthe, Herlila; Hari Prihanto, Purwaka; Achmad, Erni (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2024)
This study aims to analyze the social and economic conditions of rubber farmers in the Muhajirin Village, Jaluko District, Muaro Jambi Regency. In addition, it is also to analyze the factors that influence rubber production in Muhajirin Village, Jaluko District, Muaro Jambi Regency. The type of data used in this study is primary data obtained through a survey using a questionnaire. Samples of rubber farmers who were respondents in this study were 82 farmers. The analytical method used in this research is descriptive quantitative using multiple linear regression analysis tools. This study aims to analyzethe factors that have a significant influence in this study are land area, number of plants, number of tapping and labor. Furthermore, age of plant does not have a significant effect on the amount of rubber production in Muhajirin Village, Jaluko District, Muaro Jambi Regency